Interleukin‐4 and Interleukin‐17 are associated with coronary artery disease - Wang, Chenyang; Liu, Sheng; Yang, Yunxiao; Kamronbek, Raimov; Ni, Siyao; Cheng, Yunjiu; Zhou, Can; Yan, Huiyuan; Li, Li; Liu, Hao; Wang, Yu; Qin, Yanwen; et al. (Clinical cardiology (Mahwah, N.J.), 2024)
Introduction The present study aimed to examine the correlation between serum cytokine levels and the incidence of coronary artery disease (CAD), a leading cause of mortality globally, which is known to have a strong association with inflammatory factors. The study further sought to determine the predictors of CAD to distinguish patients with coronary artery lesions from those suspected of having CAD. Methods and Results In this study, 487 patients who underwent coronary angiography as a result of suspected CAD but without acute myocardial infarction (AMI) were recruited. The serum levels of the cytokines interleukin (IL)‐1β, IL‐2, IL‐4, IL‐5, IL‐6, IL‐8, IL‐10, IL‐12p70, IL‐17, tumor necrosis factor‐α, interferon (IFN)‐α, and IFN‐γ were measured using a multiplexed particle‐based flow cytometric assay technique. The results of the study revealed that the levels of IL‐4, IL‐12p70, IL‐17, IFN‐α, and IFN‐γ in the CAD group were significantly lower compared to those in the non‐CAD group. Multivariate logistic regression analysis indicated that two serum cytokines (IL‐4 and IL‐17), one protective factor (high‐density lipoprotein cholesterol [HDL‐C]), and three risk factors (sex, smoking, and diabetes) were independently predictive of CAD. The receiver operating characteristic curve analysis showed that the combined use of these predictors in a multivariate model demonstrated good predictive performance for CAD, as evidenced by an area under the curve value of 0.826. Conclusion The results of the study indicated that serum IL‐4 and IL‐17 levels serve as independent predictors of CAD. The risk prediction model established in the research, which integrates these serum cytokines (IL‐4 and IL‐17) with relevant clinical risk factors (gender, smoking, and diabetes) and the protective factor HDL‐C, holds the potential to differentiate patients with CAD from those suspected of having CAD but without AMI. This study included 487 patients who underwent coronary angiography (CAG) as a result of suspected coronary artery disease (CAD) but without acute myocardial infarction (AMI). Cytokine levels were measured. IL‐4 and IL‐17, along with high‐density lipoprotein cholesterol (HDL‐C), sex, smoking, and diabetes, independently predicted CAD. A combined model demonstrated good predictive performance for CAD.